If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 7 + 3u Solving 13 = 7 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 13 + -3u = 7 + 3u + -3u Combine like terms: 3u + -3u = 0 13 + -3u = 7 + 0 13 + -3u = 7 Add '-13' to each side of the equation. 13 + -13 + -3u = 7 + -13 Combine like terms: 13 + -13 = 0 0 + -3u = 7 + -13 -3u = 7 + -13 Combine like terms: 7 + -13 = -6 -3u = -6 Divide each side by '-3'. u = 2 Simplifying u = 2
| 5x+7=-38-6x | | 3log(x)-4log(x+3)+log(y)= | | 9x*2-25y*2=-1 | | 1+4x=1+x | | 5y^2=35 | | -0.8w=5 | | p-24=4(5p-6) | | -38x+76= | | 3ln(x)-4ln(x+3)+ln(y)= | | 5(x+1)=3x(x+4) | | 37-4x=9-8x | | 3ln(x^2)=10 | | -4c-2=19 | | 3lnx^2=10 | | 8+4n=-6(-4-n) | | x^3y-4xy=0 | | 5+b= | | 2x+lne^4x=12 | | 2x+lne=12 | | (10*9+5*5)*28=x | | 4(x+2)=2(x+5) | | (10*9+5*5)=x | | 5u-7u=-8 | | 5a^2-8a-31=-10 | | 51ln(1-x)=ln(1-46x) | | (10*8+5*5)*28=x | | -28+7m=-4(4m+7) | | -1=-3/4(m+7) | | x^3-4xy=0 | | -18-11x=36 | | 100-128x=2 | | 8(x-9)=8x+-72 |